A3_2 Sucking the sea dry - McQuade, Gregor; Walker, Michael; Garland, Lee; Bradley, Thomas (Physics Special Topics, 2014)
This paper discusses the possibility of removing water from the earth into space using only capillary action. The paper finds that a capillary of radius 2.332x10^-10 would be required meaning that though theoretically possible not realistically plausible to create.